2014
DOI: 10.1093/jisesa/ieu039
|View full text |Cite
|
Sign up to set email alerts
|

Biology, Predation, and Life Table of Cydnoseius negevi and Neoseiulus barkeri (Acari: Phytoseiidae) on the Old World Date Mite, Oligonychus afrasiaticus (Acari: Tetranychidae)

Abstract: The old world date mite, Oligonychus afrasiaticus (McGregor) (Acari: Tetranychidae) is a severe spider mite pest of date palm in most of the Middle East and North Africa. Considering that nothing is known about the performance of phytoseiid predators against O. afrasiaticus , biology, predation, and life table parameters of Cydnoseius negevi (Swirski and Amitai) and Neoseiulus barkeri Hughes (Acari: Phytoseiidae), collected from date palm orchards, were studied under laboratory conditions (25, 35°C and 35 ± 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
23
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
(40 reference statements)
7
23
1
2
Order By: Relevance
“…Oligonychus afrasiaticus (McGregor) is a widespread species of spider mites infesting the fruits of date palm in Middle East (Saudi Arabia [ 2 ], Oman [ 3 ], Iraq [ 4 ], Iran [ 5 ], Egypt [ 6 ], Israel [ 7 ], Yemen [ 8 ]), and North Africa (Tunisia [ 9 ], Algeria [ 10 ]). The infestation of old world date mites starts after fruit set and multiply logarithmically on the kimri stage of the fruit by spinning silken webs around date bunches [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oligonychus afrasiaticus (McGregor) is a widespread species of spider mites infesting the fruits of date palm in Middle East (Saudi Arabia [ 2 ], Oman [ 3 ], Iraq [ 4 ], Iran [ 5 ], Egypt [ 6 ], Israel [ 7 ], Yemen [ 8 ]), and North Africa (Tunisia [ 9 ], Algeria [ 10 ]). The infestation of old world date mites starts after fruit set and multiply logarithmically on the kimri stage of the fruit by spinning silken webs around date bunches [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The predatory mite, Neoseiulus barkeri Hughes (Acari: Phytoseiidae) is a generalist predator (McMurtry et al, 2013). Number of studies revealed the predatory potential of N. barkeri against wide range of pests including Thrips tabaci (Hansen, 1988;Bakker and Sabelis, 1989;Bonde, 1989;Jafari et al, 2013), broad mite, Polyphagotarsonemus latus (Fan and Petitt, 1994), bulb scale mites, Steneotarsonemus laticeps (Messelink and Holstein-Saj, 2007;Messelink, 2012), date mite, Oligonychus afrasiaticus (Negm et al, 2014) and Aleuroglyphus ovatus (Xia et al, 2012). Keeping in view, the predatory potential of this predatory mite, the focus is to use selective pesticides along with it which are least toxic for this predator.…”
Section: Introductionmentioning
confidence: 99%
“…Existen variaciones en susceptibilidad a las condiciones de baja humedad entre las especies y "strains" que habitan diferentes regiones climáticas. En las especies de zonas húmedas, la eclosión de las larvas a una humedad relativa por debajo del 60% y temperaturas que van desde 20 a 32 ºC es cero o muy baja, mientras que la eclosión de larvas de especies de zonas áridas ocurre a humedades de alrededor del 30% y a temperaturas que van de 20 a 25 ºC (Negm et al, 2014). De acuerdo con los antecedentes anteriores se planteó evaluar el efecto de la humedad relativa en la viabilidad de huevos de Neoseiulus sp.…”
Section: Introductionunclassified
“…Esto es especialmente cierto para ácaros de la familia Phytoseiidae y particularmente para sus huevos (Ferrero et al, 2010). La tolerancia de los huevos a una baja humedad relativa en la familia Phytoseiidae puede relacionarse con el ambiente en el que han evolucionado sus especies (Negm et al, 2014). Al respecto, C. picanus, otro fitoseido colectado en el ambiente desértico de Pica por Ragusa (Ragusa, 2000) mostró una gran tolerancia a la baja humedad relativa con un 40% de eclosión de larvas a 42,35 ± 5,01% HR (23,7 hPa) y 29,44 ± 1,47 ºC (Tello et al, 2009).…”
unclassified